Seven Billion Microcosms: Evolution within Human Microbiomes - Lieberman, Tami D. (mSystems, 2018)
Rational microbiome-based therapies may one day treat a wide range of diseases and promote wellness. Yet, we are still limited in our abilities to employ such therapies and to predict which bacterial strains have the potential to stably colonize a person. The Lieberman laboratory is working to close this knowledge gap and to develop an understanding of how individual species and strains behave in the human microbiome, including with regard to their niche ranges, survival strategies, and the degree to which they adapt to individual people. We employ system-level approaches, with a particular emphasis on using de novo mutations and evolutionary inference to reconstruct the history of bacterial lineages within individuals.